PENETAPAN NILAI SPF (SUN PROTECTION FACTOR) SEDIAAN KRIM TABIR SURYA DI KOTA BANDAR LAMPUNG DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Subur Widodo; Akhmad Rokiban; Lilik Koernia Wahidah; Ikhrami Nurjannah (JFL : Jurnal Farmasi Lampung, 2023)
Nowadays people awareness of the healthy skin importance is increasing, this is evident by the increasing cosmetic brands and there are many beauty clinics. Cosmetic products marketed should have the same efficacy as those listed on the packaging. Therefore, determining the efficacy of sunscreen preparations is very important to see the compliance of cosmetics manufacturers. The purpose of this study was to determine the suitability of the SPF product efficacy. The samples are the products which have SPF 30, the sample was tested by in vitro method using UV-Vis spectrophotometer, every 5 nm with the wavelength range 290 nm - 320 nm absorbance was measured, then analyzed with the mansur equation. Also did antioxidant activity tested with vitamin C as a control positive using the DPPH method. The principle of the DPPH method is the measurement of absorbance of DPPH radicals which are degraded due to the presence of antioxidant compounds using a UV-Vis spectrophotometer. The decrease in DPPH absorbance intensity is proportional to the increase in the concentration of antioxidant compounds expressed in IC50 (Inhibition Concentration 50). Sample 4 has an SPF value close to the value written on the packaging. Samples 2, 5, 1, 3, 6, 7 and 8 have SPF values ​​smaller than those listed on the packaging. The antioxidant activity obtained is rateable to the SPF value, sample 4 has the highest antioxidant activity followed by sample 2, sample 5, sample 1, sample 3, sample 6, and sample 7 and sample 8 have the lowest antioxidant activity. Keywords: Antioxidant , DPPH, UV-Vis spectrophotometry, SPF, Sunscreen